A molecular and immunohistochemical study of 37 cases of ovarian Sertoli-Leydig cell tumor - Němejcová, Kristýna; Hájková, Nikola; Krkavcová, Eva; Kendall Bártů, Michaela; Michálková, Romana; Šafanda, Adam; Švajdler, Marián; Shatokhina, Tetiana; Laco, Jan; Matěj, Radoslav; Hausnerová, Jitka; Škarda, Jozef; et al. (Virchows Archiv, 2025)
This study provides an analysis of 37 ovarian Sertoli-Leydig cell tumors (SLCT), focusing on their morphological, immunohistochemical, and molecular features. The cohort was comprised of 9 well-differentiated, 25 moderately differentiated, and 3 poorly differentiated tumors. The immunohistochemical analysis was performed with 28 markers, including diagnostic markers and markers with possible predictive significance. The results showed high expression of sex cord markers (FOXL2, SF1, inhibin A, CD99, calretinin, ER, PR, AR), and variable expression of other markers such as CKAE1/3 (83%), CAIX (14%), and MUC4 (1%). Loss of PTEN expression was present in 14% of cases, and CTLA4 expression was seen in 43% of cases. All tumors were MMR proficient and HER2 and PD-L1 negative. The molecular analysis showed DICER1 mutations in 54.5% of cases, and a FOXL2 mutation in 6% of tumors. In addition, we detected 2 cases with TERT promoter mutation. RNA NGS sequencing identified significant differences in mRNA expression between DICER1MUT and DICER1WT tumors. The DICER1WT tumors showed increased expression of PRKCA, HNF1A, LDLR, and MAP2K5. On the contrary, the DICER1MUT cases showed increased expression of CDK6, NOTCH2, and FGFR2. The results of our study show that SLCTs exhibit distinct molecular features based on their degree of differentiation. We have confirmed that DICER1 mutations are characteristic of moderately and poorly differentiated SLCTs, while well-differentiated SLCTs may represent a distinct entity. DICER1MUT and DICER1WT tumors showed different mRNA expression profiles. The FOXL2 mutation is less common in these tumors and is mutually exclusive with the DICER1 mutation.
Keywords: Ribonuclease III; Adolescent; Sertoli–Leydig cell tumor; Ovarian Neoplasms; Adult; senioři; Ovarian tumors; Aged; Immunohistochemistry; lidé; lidé středního věku; Humans; Mutation; Middle Aged; Biomarkers, Tumor; nádorové biomarkery; Sex cord-stromal tumor; Young Adult; protein FOXL2; ribonukleasa III; nádor ze Sertoliho-Leydigových buněk; Forkhead Box Protein L2; DEAD-box RNA Helicases; dospělí; mladý dospělý; Sertoli-Leydig Cell Tumor; imunohistochemie; DICER1; ženské pohlaví; mladiství; MRNA expression; mutace; Female; DEAD-box RNA-helikasy; nádory vaječníků